ANALISIS PEMANFAATAN E-MUSRENBANG DKI JAKARTA SEBAGAI SARANA PARTISIPATIF DALAM PROSES PEMBANGUNAN - Hasanah, Rizka Luluatul; Azahra, Shalwa; Aprilia, Aisyah Dwi; Nurdin, Nurdin (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This research aims to analyze the utilization of DKI Jakarta E-Musrenbang as a participatory tool in the regional development planning process. E-Musrenbang comes as a digital innovation that supports transparency, efficiency, and direct community involvement through information technology. This research uses a descriptive qualitative approach with secondary data analyzed to understand the effectiveness of application implementation as well as the driving and inhibiting factors for its use. The results of this study show that E-Musrenbang is able to improve accessibility and transparency in conveying aspirations from the community. However, it is still not free from challenges such as low digital literacy, limited infrastructure, lack of socialization, and weak follow-up to community proposals are still significant obstacles in optimizing public participation. The findings are expected to be an input for the development of more inclusive and participatory public policies in the digital era.